MODEL PERUBAHAN TUTUPAN LAHAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Pribadi, Didit Okta (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Urban and regional development needs space and land which then replaces the existence of natural space. The loss of natural space does not give negative impacts as long as it does not exceed ecological carrying capacity.Unfortunately, urban and regional development in Indonesia is dominated by economy motivation than ecology consideration. As a result, several natural disasters occurred such as flood, ground water depletion, land slides etc. Our research objective is to analyze land cover change from natural space to human activity space and several factors which cause it at 4 different regions: Malang Municipal, Batam Municipal, Pemalang Regency and Muaro Jambi Regency. Research result could be used as basic information for local government to arrange planning, use and control spatial change in each area. This research was conducted by using two different time data images with interval 10 years to get land cover change on each region and social economy data from National Statistic Bureau. The model was formulated by using forward stepwise multiple regressions and the result showed that each region has different factors which increase land cover change of natural space such as: (1) Malang Municipal was dominantly influenced by urban sprawl phenomenon, (2) Batam Municipal wasdominantly influenced by government policy to develop industry, (3) Pemalang Regency was dominantly influenced by appearance of several new growth poles, and (4) Muaro Jambi Regency was dominantly influenced by land necessity for agriculture activities.